The Influence of Positive Emotion and Sports Hope on Pre-competition State Anxiety in Martial Arts Players - Yang, HuiXin; Wen, XuPing; Xu, Fei (Frontiers in Psychology, 2020)
Objectives: The present study proposes a model for the relationships among competitive martial arts players' positive emotions, hope (path and emotive force ideas), sense of control, self-handicapping and pre-competition state anxiety (PCSA). The model seeks to advance our understanding around the causal and mediating effects between these variables, and thus has important implications for theory and practice in the field of sports and exercise psychology. Method: A total of 327 participants (male255, male: 72; age: 21.45 ± 2.78 years; athletic training: 6.27 ± 2.54 years) in the China University Wushu Sanda Championship 2019 were surveyed. Within 2 hours before the match, PCSA, sports hope, sense of control, anxiety, and self-handicapping were measured. Results: The findings of the present study showed that 1) Positive emotions have a significant positive correlation with path and emotive force ideas, anxiety orientation, ability to cope, goal attainment, and sense of control; 2) path and emotive force ideas were significantly positively correlated with anxiety orientation, ability to coping, goal attainment, and sense of control, and significantly negatively correlated with anxiety intensity and self-handicapping; 3) Path idea acted as a partial negative mediator between positive emotion and anxiety intensity; the sense of control played a partial negative mediator between emotive force idea and self-handicapping. Conclusions: 1) Players' positive emotions can predict the sense of hope. It also tends to interpret the anxiety intensity as a positive challenge rather than the negative sense of control; 2) players with higher path idea also tend to have a lower negative emotion, anxiety intensity, and self-handicapping; 3) martial arts players' path idea has a significantly higher predictive power for the sense of control than emotive force idea. Still, both path and emotive force ideas can indirectly affect the intensity of anxiety orientation and self-handicapping through the multiple mediators of sense of control. Finally, recommendations for coaches related to training and preparation for competition are discussed.